Impact of Financial Literacy on Household Decision-Making: A Study in the State of West Bengal in India - Biswas, Shubhra; Gupta, Arindam (International Journal of Economics and Financial Issues, 2021)
The study assesses the status of financial literacy in West Bengal and finds its impact on household decision-making of 600 respondents from eight selected districts of the state. Financial literacy of female and rural respondents is found to be lower. Higher income and education remain the other significant determinants of financial literacy. Financial literacy is found to significantly affect saving decision, investment decision, borrowing propensity and borrowing quality, the first three being positively and fourth being negatively influenced by financial literacy. However, on retirement planning no significant impact is observed. Keywords: Financial literacy, Household decision making, Retirement planning, Borrowing quality JEL Classifications: D15, G51, G53, J32 DOI: https://doi.org/10.32479/ijefi.11759